2005
DOI: 10.1210/me.2005-0148
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Juxtamembrane Segment of the V1a Vasopressin Receptor Provides Two Independent Epitopes Required for High-Affinity Agonist Binding and Signaling

Abstract: It is fundamentally important to define how agonist-receptor interaction differs from antagonist-receptor interaction. The V1a vasopressin receptor (V1aR) is a member of the neurohypophysial hormone subfamily of G protein-coupled receptors. Using alanine-scanning mutagenesis of the N-terminal juxtamembrane segment of the V1aR, we now establish that Glu54 (1.35) is critical for arginine vasopressin binding. The mutant [E54A]V1aR exhibited decreased arginine vasopressin affinity (1700-fold) and disrupted signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…F, wild-type with GnRH I/GnRH II, E, wild-type with Pro 9 -NHEt analogs; f, R38A with GnRH I/GnRH II; Ⅺ, R38A with Pro 9 -NHEt analogs; OE, R38K with GnRH I/GnRH II; ‚, R38K with Pro 9 -NHEt analogs. Studies on other peptide GPCRs have also shown that the extracellular end of TM 1 is important for high affinity binding of peptide agonists (Silvente-Poirot et al, 1998;Anders et al, 1999;Wesley et al, 2002;Hawtin et al, 2005;Marco et al, 2007). Mutation of the residue Glu 1.35 of the V 1a vasopressin receptor (which is positionally equivalent to Arg 38(1.35) and is totally conserved among vasopressin and oxytocin receptors) to alanine leads to a 1700-fold decrease in affinity for peptide agonist vasopressin but has no effect on peptide antagonist binding affinity (Hawtin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F, wild-type with GnRH I/GnRH II, E, wild-type with Pro 9 -NHEt analogs; f, R38A with GnRH I/GnRH II; Ⅺ, R38A with Pro 9 -NHEt analogs; OE, R38K with GnRH I/GnRH II; ‚, R38K with Pro 9 -NHEt analogs. Studies on other peptide GPCRs have also shown that the extracellular end of TM 1 is important for high affinity binding of peptide agonists (Silvente-Poirot et al, 1998;Anders et al, 1999;Wesley et al, 2002;Hawtin et al, 2005;Marco et al, 2007). Mutation of the residue Glu 1.35 of the V 1a vasopressin receptor (which is positionally equivalent to Arg 38(1.35) and is totally conserved among vasopressin and oxytocin receptors) to alanine leads to a 1700-fold decrease in affinity for peptide agonist vasopressin but has no effect on peptide antagonist binding affinity (Hawtin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on other peptide GPCRs have also shown that the extracellular end of TM 1 is important for high affinity binding of peptide agonists (Silvente-Poirot et al, 1998;Anders et al, 1999;Wesley et al, 2002;Hawtin et al, 2005;Marco et al, 2007). Mutation of the residue Glu 1.35 of the V 1a vasopressin receptor (which is positionally equivalent to Arg 38(1.35) and is totally conserved among vasopressin and oxytocin receptors) to alanine leads to a 1700-fold decrease in affinity for peptide agonist vasopressin but has no effect on peptide antagonist binding affinity (Hawtin et al, 2005). The equivalent residue Arg 1.35 in the cholecystokinin-2 receptor has also been shown to be important for peptide ligand binding (Silvente-Poirot et al, 1998;Marco et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to R46, Glu-54 (E54) is also critical for the binding of V1a receptor agonists. R46, which is located just outside TM1, and E54 in TM1 near R46, are conserved in other members of mammalian AVP/OT receptor families and also in other vertebrate and invertebrate nonapeptide receptor families, such as the vasotocin (AVT) receptor for invertebrates, and isotocin and mesotocin receptors for fish and birds (204,209,210).…”
Section: A Ligand Binding and Selectivitymentioning
confidence: 99%
“…It has also been reported that the N termini of the V 1a R and OTR are required for agonist binding (12,13). In particular, two charged residues (Arg 46 and Glu 54 ) in the V 1a R N terminus are required for high affinity agonist binding but not antagonist binding (14,15). Likewise, Arg 34 in the N terminus of the OTR is required for agonist binding (16).…”
mentioning
confidence: 99%